Islam dan Demokrasi: Kajian Pemikiran Teologis dan Praktik Politik di Indonesia - Vindy Rina Auliasari; Mukhsin Achmad (STIKes Ibnu Sina Ajibarang, 2025)
Islam and democracy are often considered two concepts with fundamental differences, particularly in terms of sovereignty, law, and decision-making processes. However, in the context of Indonesia, these two concepts have interacted in a unique and dynamic way. As the largest democratic country with a Muslim majority, Indonesia serves as a social laboratory for testing the compatibility between Islam and democracy. This research examines the Muslim community's response to democracy through two main approaches: theological thinking rooted in Islamic values such as syura (consultation), ‘adalah (justice), and musawah (equality), as well as political practices reflected in Muslim participation in Indonesia's democratic system. Furthermore, this research explores the role of Islamic organizations such as Nahdlatul Ulama (NU) and Muhammadiyah in promoting inclusive democracy, as well as the challenges faced, such as radicalism and identity politics. The research findings indicate that Islam is not only compatible with democracy but also enriches democratic values through ethical and moral principles. Thus, this paper provides an important contribution to understanding the relationship between Islam and democracy, particularly in the Indonesian context.